2015
DOI: 10.1039/c5ra07080e
|View full text |Cite
|
Sign up to set email alerts
|

Toward bioenergy recovery from waste activated sludge: improving bio-hydrogen production and sludge reduction by pretreatment coupled with anaerobic digestion–microbial electrolysis cells

Abstract: aIn this study, a novel technology named pretreatment coupled with anaerobic digestion-microbial electrolysis cells (AD-MECs) for waste activated sludge (WAS) reduction and renewable bioenergy recovery has been investigated. The results showed that, compared with the control pretreatment, the three pretreatment methods used greatly enhanced the performance of the AD-MECs process, and efficient sludge reduction was achieved, especially in heat-alkaline pretreatment, 36.9% and 46.7% for total suspended solid (TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…[3][4][5] Waste activated sludge (WAS) is greatly generated as the by-product of wastewater treatment plants. [6][7][8] It has been reported that the content of P in dried sludge is around 2% in the conventional activated sludge process and 4-10% in the enhanced biological phosphorus removal process. 9 Considering the high production amount and P content of WAS, it can be an alternative P resource.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Waste activated sludge (WAS) is greatly generated as the by-product of wastewater treatment plants. [6][7][8] It has been reported that the content of P in dried sludge is around 2% in the conventional activated sludge process and 4-10% in the enhanced biological phosphorus removal process. 9 Considering the high production amount and P content of WAS, it can be an alternative P resource.…”
Section: Introductionmentioning
confidence: 99%
“…With the conventional disposal routes coming under pressure, more cost-effective and environmentally benign alternatives for WAS are needed. Currently, due to its carbonaceous characteristics (organics possess 90–95% in dry weight), WAS is considered as a renewable and utilizable biomass resource and gained worldwide attention [35]. Cost-effective microbial conversion from WAS by anaerobic digestion to specific valuable products is an innovative and promising way to gain social and economic benefits.…”
Section: Introductionmentioning
confidence: 99%